Does nutritional status affect treatment tolarability, response and survival in metastatic colorectal cancer patients? Results of a prospective multicenter study. (August 2021) - Karabulut, Senem; Dogan, Izzet; Usul Afsar, Cigdem; Karabulut, Mehmet; Karaman, Sule; Ferhatoglu, Ferhat; Tastekin, Didem
Background: The efficacy and tolerability of modern cytotoxic chemotherapy regimens used in malnourished metastatic colorectal cancer (mCRC) patients is uncertain. The aim of this study was to investigate the effect of malnutrition on efficacy and tolerability of cytotoxic chemotherapy and overall survival in mCRC patients. Methods: In this multicenter study, demographic, oncologic and nutritional data were collected prospectively from mCRC patients. Nutritional status of the patients were evaluated on the basis of NRI (Nutritional Risk Assessment), BMI (Body Mass Index) and WL (Weight Loss) before the first chemotherapy, after the first and second chemotherapy during 2 cycles of chemotherapy every 15 days. To determine the inter-treatment weight loss toxicity assessment was included to theese parameters after each chemotherapy. NRI calculation was performed as [1.51xserum albumin level (g/L)+41.7xcurrent weight/basic weight]. NRIs were examined in 3 categories as 'no malnutrition' (NRI >97.5), 'moderate malnutrition' (97.5 ≥NRI ≥83.5) or 'severe malnutrition' (NRI <83.5). Response to treatment and drug-induced toxicities were assessed based on Criteria in Solid Tumors (RECIST) 1.1 and National Cancer Institute CTCAE version 4.0 respectively. Results: One-hundred and thirty-seven mCRC patients were prospectively included. Median age was 48 (range 18-83). Primary location was colon in 66% of patients and 84% of their primary source was left colon. Malnutrition was detected in 39% of the cases. Response rate to treatment was twenty four percent. While there was no significant relationship between chemotherapy response and moderate/severe malnutrition (p = 0.24), moderate/severe malnutrition was associated with multipl site of metastases, WHO PS (World Health Organization Performance Status) of 1, over the median value of CEA/CA 19-9 (carcinoembryonic antigen/carbohydate antigen 19-9) levels (p = 0.003, p = 0.03, p < 0.001, and p = 0.02; respectively). Hypoalbuminemia and moderate/severe malnutrition were associated with all types of toxicity (p < 0.001 and p < 0.001). Moderate/severe malnutrition was associated with thrombocytopenia, and diarrhea following chemotherapy predominately, (p = 0.02 and p = 0.04; respectively). In moderate/severe malnutrition group median overall survival was prominently shorter than those with no malnutrition [6.6 moths (95%CI, 5.6-7.6) vs 11.9 moths (95% CI, 11.1-12.7) respectively, p < 0.001]. Conclusions: Our study showed that moderate/severe malnutrition in mCRC patients was associated with decreased overall survival and increased chemotherapy toxicity.